Huntingtin, signaling endosomes and neuronal survival in health and Huntington disease - Myriam Saliba; Frédéric Saudou; Chiara Scaramuzzino (Journal of Huntington's Disease, 2026)
The axonal transport of organelles mediates several functions throughout the lifespan of neurons. Over the past years, the role of endosomes, a specific type of trafficking organelle, has been extensively investigated for their increasing relevance during development, maturation and maintenance of neuronal networks. Endosome formation results from membrane invagination events driven by endocytic pathways. Following their formation, endosomes undergo maturation steps, and their fate is determined by the recruitment of specific cytosolic proteins to their membrane. Early endosomes may be recycled, signal in the distal compartments (signaling endosomes) or undergo fusion with autophagosomes (amphisomes), thus entering the degradation pathways together with lysosomes. Altogether, these processes regulate plasma membrane equilibrium at the synapse, further recycling and degradation of dysfunctional or toxic proteins, and promote the distribution of fundamental signals far from the synapses. Many of these pathways involve huntingtin (HTT) functions and are impaired in Huntington disease (HD). The past years have shed light on newly identified mechanisms involving the endocytic machinery with special attention being paid to long-range signaling endosome trafficking in axons. In this review, we will summarize the recent advancements and discuss the potential implications of therapeutic approaches to rescue these processes in the context of HD.